Teoremas de comparação para o núcleo do calor de subvariedades mínimas e aplicações - Chaves, Francisco Pereira (2016)
In this work we will prove comparison results for the heat kernel of minimal submanifolds in Riemannian manifolds with sectional curvature bounded above by the curvature of a model manifold. Next we will obtain results about the L1-Liouville property of Riemannian submersions with minimal fibers. Finnaly, we will prove inequalities for the weighted fundamental tone of transversally foliated subsets of weighted Riemannian manifolds in terms of the weighted mean curvatures of the leaves of the foliation.